PENERAPAN PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN PEMAHAMAN PENJUMLAHAN BILANGAN BULAT DI SD 121 ONODOWA - Herling Wungko; Erwin Nurdansyah; Mulyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Using a contextual approach, this study seeks to enhance fourth graders' comprehension of integer addition at SDN 121 Onodowa. PTK was used in this study; it consists of two phases: planning and action implementation, followed by observation and reflection. The participants in the study were twenty-two fourth graders. Learning outcome exams, documentation, and observation were used to gather data. Based on the development of students' learning outcomes in each cycle, the data were analysed using descriptive quantitative and qualitative methods. The results demonstrated that students' comprehension of integer addition was enhanced upon implementing the contextual approach. From 70 in the pre-cycle stage to 78 in Cycle I and 80 in Cycle II, the average class score improved significantly. Also, from 45.45% in the pre-cycle stage to 59.09% in Cycle I and 86.36% in Cycle II, the students' learning mastery percentage grew significantly. These results show that fourth graders at SDN 121 Onodowa significantly improved their comprehension of integer addition when taught using the contextual method.